Job marginalization and its impact on the quality of the career path of a public official - Gharbi, Nadjah (Journal of Human Sciences, 2022)
This study talk about the scourge of professional exclusion in the administrative field. The latter which reflects an abuse of authority and powers attributed within the civil service on one authority. And which affects the quality of the professional career of the public official through the various forms of psychological pressure exerted on the latter, which subsequently harms the administration of public financial assets, constitutes, at the same time, one of the first causes of abandonment of the workstation. We wonder if the Algerian legislator has dealt with this phenomenon? We concluded that the absence of legal texts protecting civil servants from professional exclusion and the difficulty of proving it because it is an invisible fact, made him a victim and unable to resort to justice to argue its law, which led to the phenomenon is amplifying within various public institutions.